Dream quality and sleep paralysis in medical students - Huamaní, Charles (2006)
Introduction: Sleep paralysis is a conscious state body immobilization event that appears spontaneously or secondarily to stress situations or to possible bad quality of dream. Objective: To determine medical students association and risk of sleep paralysis in bad sleepers. Design: Analytical, transversal study. Setting: Faculty of Medicine, San Marcos Major National University. Participants: Medical students. Interventions: In May 2006, a non probabilistic sample of medical students was done by a survey including Pittsburg’s Sleep Quality Index and question referred to sleep paralysis. We determined the association between sleep paralysis and dream quality and the sleep paralysis risk in bad sleepers. Chi square test for qualitative variables and student t for quantification were used, with 95% confidence interval. Main outcome measures: Experiences in sleep paralysis and prevalence of bad sleepers. Results: Mean age was 22,3+2,7 years, 55,5% women. Information of sleep paralyses experiences during the last month was given by 26,6% (21,6-32,1%), and bad sleepers prevalence was 48,5% (42,6-54,3%). There was no association between both variables (x2 , p = 0,1; OR = 1,54; IC95: 0,9-2,6). Conclusions: There was no association between sleep paralysis and bad dream quality, differing with previous studies; we suggest to investigate on other factors that may release it.